Improving quality education through strategic performance measurement system in a state university in the Philippines - Armas, Kenneth L; Siat, Gregg O; Santos, Angelo R (International Journal of Innovative Research and Scientific Studies, 2025)
This study introduces an improved Strategic Performance Measurement System (SPMS) tool to enhance performance management and governance in Philippine public universities. With increasing expectations from stakeholders, a structured evaluation framework is essential. Using four key perspectives—financial stewardship, stakeholder engagement, internal processes, and learning and development—this study develops an integrated SPMS model with key performance indicators (KPIs) aligned with institutional goals. A qualitative approach was employed, incorporating stakeholder consultations and thematic analysis to identify critical concerns. The findings highlight the need for a transparent and responsive system to track performance in financial sustainability, academic excellence, community engagement, and global collaboration. The proposed SPMS enhances governance by integrating daily operations with long-term objectives, fostering accountability, and driving continuous improvement. This study provides a practical framework for optimizing university performance, ensuring sustainability, and cultivating a culture of innovation. Its findings offer valuable insights for policymakers and administrators seeking to align institutional strategies with measurable outcomes in higher education.